The Effectiveness of Population Service Innovation Through the Pecel Breakfast Program in Madiun Regency - Susul Setiono; Dandy Wirawan; Zainal Fatah (International Journal of Social Welfare and Family Law, 2026)
Public services in the digital era demand a more responsive and inclusive bureaucratic transformation to fulfill citizens' basic rights in population administration. In Madiun Regency, geographical constraints, complex bureaucracy, and low digital literacy are major challenges in service accessibility. In response, the Population and Civil Registration Office launched the "Sarapan Pecel" (Advanced Population Administration System in Rural Areas, Effective, Fast, and Direct Service) innovation, which decentralizes services to the village level through the use of Electronic Signatures (TTE) and the role of "Duta Pecel" as local operators. This study aims to analyze the effectiveness of the program using a descriptive qualitative approach through in-depth interviews, observations, and documentation studies. The results show that the "Sarapan Pecel" program is effective in reducing bureaucratic red tape, increasing time and cost efficiency for the community, and successfully overcoming geographical barriers. The role of village operators has proven crucial in mitigating technological culture shock and building public trust in the validity of digital documents. However, operational effectiveness still faces technical challenges such as internet network stability, electricity supply, and central server performance. As a recommendation, local governments need to strengthen physical infrastructure, regularly standardize technical competencies for village operators, and expand digital literacy strategies in a structured manner. The sustainability of these innovations depends on synchronizing the reliability of digital systems and strengthening the supporting ecosystem at the local level.